Effects of long term exposure to aluminium stress on the accumulation and distribution of K+, Na+, Ca2+, Mg2+, Fe2+ and Clin rice and chickpea plants - Samad, Rifat; Rashid, Parveen; Karmoker, JL (Dhaka University Journal of Biological Sciences, 2018)
Sand culture experiments were undertaken to examine the effect of increasing aluminium levels (50-150 μM) on the mineral nutrients uptake (K+, Na+, Ca2+, Mg2+, Fe2+ and Cl-). Increasing concentrations of Al inhibited the uptake of K+, Ca2+, Mg2+ and Fe2+ but enhanced that of Na+ and Cl- in the root and shoot of rice, and the root, stem and leaves of chickpea. 150 μM Al caused a maximum inhibition of K+ accumulation in the root and shoot of rice ranging from 25.5 to 49.0% and 33 to 55.5%, respectively, from 7 to 28 day of treatment. In the root, stem and leaves of chickpea, 150 μM Al inhibited K+ content by 23.9 to 84.0%, 13.2 to 54.4% and 25.3 to 61.2%, respectively, from 7 to 28 day of application. On the contrary, a dramatic 2.7 to 3.1-folds and 70.8% to 2.3-folds stimulation of Na+ accumulation was recorded in the root of rice and chickpea, respectively, following 100 μM Al treatment from 7 to 28 day of treatment. Different concentrations of aluminium led to a stimulation of Cl- accumulation in different parts of rice and chickpea plants. In rice and chickpea plants, the inhibitory effect of aluminium stress on the accumulation of Ca2+, Mg2+ and Fe2+ was enhanced with the increase in Al concentration from 50 to 150 μM. Dhaka Univ. J. Biol. Sci. 27(1): 37-48, 2018 (January)